Parental singing during kangaroo care: parents' experiences of singing to their preterm infant in the NICU - Hugoson, Pernilla; Haslbeck, Friederike Barbara; Ådén, Ulrika; Eulau, Louise (Frontiers in Psychology, 2025)
IntroductionSinging fosters emotional connections, attachment, bonding, and language development in infants. Prematurely born infants, however, are at risk of missing this vital communication, impacting neurodevelopment and family wellbeing, especially during prolonged hospital stays. Kangaroo care provides physiological and emotional support, while Creative Music Therapy (CMT) has demonstrated positive effects on neurodevelopment, parental wellbeing, and attachment. The Singing Kangaroo project, a Swedish-Finnish multi-center randomized controlled trial (RCT), investigated the impact of parental singing during kangaroo care. This qualitative follow-up study explores these findings through the lens of Antonovsky's Sense of Coherence (SOC) model.MethodSemi-structured interviews were conducted with 28 families (20 intervention group, eight control group) at their infant's 5-month corrected age. The intervention group received CMT twice weekly during kangaroo care for 4 weeks in the NICU, while the control group received standard care. Data were analyzed inductively, followed by deductive categorization within the SOC framework, focusing on its three core components: Manageability, Comprehensibility, and Meaningfulness.ResultsParents in the intervention group reported enhanced understanding of how singing fosters attachment and boosts their self-esteem, aligning with increased manageability and comprehensibility. Control group parents also experienced joy in singing, which positively influenced family wellbeing, albeit less extensively. Across both groups, singing was described as a meaningful activity that strengthened parent-infant bonding and promoted emotional connection within the family.ConclusionParental singing during kangaroo care, particularly when supported by a trained music therapist, enhances parents' sense of coherence by fostering comprehensibility, manageability, and meaningfulness. This study highlights the long-term benefits of integrating CMT into family-centered NICU care to support both infants' neurodevelopment and family wellbeing.